2016
DOI: 10.1177/0898264316645551
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Daily Stressors on Morning Cortisol Levels in Midlife and Older Retirees: The Moderating Roles of Age and Gender

Abstract: Together, better identification of the associations between daily stressors and physiological functioning will help contribute to the knowledge on ways to promote greater quality of life in retirement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…However, Bai et al 2017 found that among children acute stressors regarding social interactions and education were positively associated with single measurements of cortisol levels at waking up [ 101 ]. All other studies found no direct association between CAR, single measurements of cortisol levels at waking-up and number of acute stressors [ 25 , 102 106 ] in general and regarding caregiving of children with fragile X syndrome [ 102 ]. There were also no associations found regarding number [ 107 ] and occurrence [ 108 – 110 ] of acute stressors due to social interactions and severity of acute stressors [ 25 , 104 , 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Bai et al 2017 found that among children acute stressors regarding social interactions and education were positively associated with single measurements of cortisol levels at waking up [ 101 ]. All other studies found no direct association between CAR, single measurements of cortisol levels at waking-up and number of acute stressors [ 25 , 102 106 ] in general and regarding caregiving of children with fragile X syndrome [ 102 ]. There were also no associations found regarding number [ 107 ] and occurrence [ 108 – 110 ] of acute stressors due to social interactions and severity of acute stressors [ 25 , 104 , 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…In spite of these limitations, the current study has notable strengths, including a large and diverse sample of community-dwelling adults, diverse assessments of resting and non-stress cortisol in different contexts, a rich array of measures of psychosocial functioning and health, and an analytical approach designed to illuminate the strengths of association between different cortisol indices and psychosocial and health measures. Previous studies, including those using the cortisol data from the MIDUS cohort, have contributed well-developed models that frame our understanding of how certain cortisol indices are related to many psychosocial factors, including socioeconomic status, life satisfaction [19], well-being [23], depression [56], negative affect [57], daily stressors, positive events [7, 58, 59], and physical health [60]. This study adds to this prior work by explicating the extent to which cortisol indices used across these studies represent the same or distinct underlying aspects of HPA axis activity and the degree to which each is linked to diverse psychosocial and health factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Friedman and Ryff (2012) used the multiplicative interaction terms between the number of chronic conditions and the psychological functioning measures to examine how the effect of chronic conditions on IL-6 can be buffered by different factors, including positive relationships with others and PIL. In another study, Wong and Shobo (2017) used the regression interaction approach under the multilevel modeling to test whether the effect of daily stressor on the level of stress, measured by cortisol level, was differed by age and gender. While this method is valuable in acknowledging the contribution of prespecified moderators to buffering the negative effects of adversity, it is subject to limitations that specific hypothesis about the moderators needs to be made in advance and the differential effects are tested given the constraints of the limited set of moderators (Van Horn et al, 2015).…”
Section: Analytical Methods For Moderation Effects In Psychologicalmentioning
confidence: 99%
“…Similarly, Friedman and Ryff (2012) used the multiplicative interaction terms between the number of chronic conditions and the psychological functioning measures to examine how the effect of chronic conditions on IL-6 can be buffered by different factors, including positive relationships with others and PIL. In another study, Wong and Shobo (2017) used the regression interaction approach under the multilevel modeling to test whether the effect of daily stressor on the level of stress, measured by cortisol level, was differed by age and gender.…”
Section: Analytical Methods For Moderation Effects In Psychological W...mentioning
confidence: 99%
See 1 more Smart Citation